A two-session psychological intervention for siblings of pediatric cancer patients: a randomized controlled pilot trial - Prchal Alice; Graf Anna; Bergstraesser Eva; Landolt Markus A (BMC, 2012)
Abstract Background Since siblings of pediatric cancer patients are at risk for emotional, behavioral, and social problems, there is considerable interest in development of early psychological interventions. This paper aimed at evaluating the effectiveness of a two-session psychological intervention for siblings of newly diagnosed pediatric cancer patients. Methods Thirty siblings age 6-17 years were randomly assigned to an intervention group or an active control group with standard psychosocial care. The manualized intervention provided to siblings in the first 2 months after the cancer diagnosis of the ill child included medical information, promotion of coping skills, and a psychoeducational booklet for parents. At 4 to 6 weeks, 4 months, and 7 months after the diagnosis, all siblings and their parents completed measures (from standardized instruments) of social support, quality of life, medical knowledge, posttraumatic stress symptoms, and anxiety. Results At follow-up siblings in the intervention group showed better psychological well-being, had better medical knowledge, and reported receiving social support from more people. However, the intervention had no effects on posttraumatic stress symptoms and anxiety. Conclusions The results of this pilot trial suggest that a two-session sibling intervention can improve siblings' adjustment, particularly psychological well-being, in the early stage after a cancer diagnosis. Trial Registration ClinicalTrials.gov NCT00296907